Analysis of company’s performance: financial ratio analysis and index trend analysis: the case of Malaysian International Shipping Corporation (MISC) Berhad / Muhammad Qahhar Jusoh - Jusoh, Muhammad Qahhar (Faculty of Business and Management, 2010)
MISC is a leading shipping line of Malaysia and one of the top 10 shipping Companies in the world by market capitalization. It started off with a proposal to the National Shipping Committee of Malaysia to create a national shipping line. MISC was incorporated in 1968 as Malaysian International Shipping Corporation. In 1997 Petronas acquired 29.3% stake in MISC and later increased it to 62.3% with the injection of their Petronas Tankers into MISC. On 1998 MISC became a subsidiary of PETRONAS. This project paper focus on the analysis performance and the alternative financial evaluation methods for MISC bhd. Recently, All liner department of MISC’s used Citrix Sealiner Systems as the main tools of their operations. These systems are only uses by shipping’s company. Data being collected by referring journal, interview, observation and also experiment in order to test the new method in MISC. Thus further studies being done to find the way of introducing the alternative methods of evaluation. Ratio and index trend analysis are a methods which have been used to evaluate financial performance of the company. The first method is used to compare financial statement of the same unit over different periods. The second method are used to enable in making analysis on financial statement that covers more than three or five years period of financial statement and also to compare the financial ratios for a given company over time to detect any improvement or deterioration in a firm’s financial condition and performance. The result indicates that, the used of these two methods contribute to the evidence that based on the trend of financial statement.